The Role of Pattern-Recognition Receptors in Graft-Versus-Host Disease and Graft-Versus-Leukemia after Allogeneic Stem Cell Transplantation - Heidegger, Simon; van den Brink, Marcel R. M.; Haas, Tobias; Poeck, Hendrik (Frontiers in Immunology, 2014)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only treatment with curative potential for certain aggressive hematopoietic malignancies. Its success is limited by acute graft-versus-host disease (GVHD), a life-threatening complication that occurs when alloreactive donor T cells attack recipient organs. There is growing evidence that microbes and innate pattern-recognition receptors (PRRs) such as toll-like (TLR) and nod-like receptors (NLR) are critically involved in the pathogenesis of acute GVHD. A now widely accepted model postulates that intensive chemotherapy and / or total-body irradiation during pre-transplant conditioning result in tissue damage and a loss of epithelial barrier function. Subsequent translocation of bacterial components as well as release of endogenous danger molecules stimulate PRRs of host antigen-presenting cells (APCs) to trigger the production of pro-inflammatory cytokines (‘cytokine storm’) that modulate T cell alloreactivity against host tissues, but eventually also the beneficial graft-versus-leukemia (GVL) effect. Given the limitations of existing immunosuppressive therapies, a better understanding of the molecular mechanisms which govern GVHD vs GVL is urgently needed. This may ultimately allow to design modulators which protect from GvHD but preserve donor T-cell attack on hematologic malignancies. Here, we will briefly summarize current knowledge about the role of innate immunity in the pathogenesis of GVHD and GVL following allo-HSCT.